2018
DOI: 10.12688/wellcomeopenres.14439.1
|View full text |Cite
|
Sign up to set email alerts
|

Ethical considerations in Controlled Human Malaria Infection studies in low resource settings: Experiences and perceptions of study participants in a malaria Challenge study in Kenya

Abstract: Background: The range and amount of volunteer infection studies, known as Controlled Human Infection Model (CHMI) studies, in Low-Middle Income Countries (LMICs) is increasing with rapid technological advancement, world-class laboratory facilities and increasing capacity development initiatives. However, the ethical issues these studies present in LMICs have not been empirically studied. We present findings of a descriptive social science study nested within a malaria volunteer infection study, on-going at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
66
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(74 citation statements)
references
References 23 publications
(43 reference statements)
8
66
0
Order By: Relevance
“…Previous studies have demonstrated an inverse correlation between education and financial reward as a motivator and education, suggesting that highly educated people may be less likely to need the money or less susceptible to financial inducement 15 . As these studies were set in a high-income context the survey results may not be generalizable to low-income countries where (at present) ~7% of challenge studies are conducted 8 and the ethics of financial benefits may need a higher level of scrutiny 11 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have demonstrated an inverse correlation between education and financial reward as a motivator and education, suggesting that highly educated people may be less likely to need the money or less susceptible to financial inducement 15 . As these studies were set in a high-income context the survey results may not be generalizable to low-income countries where (at present) ~7% of challenge studies are conducted 8 and the ethics of financial benefits may need a higher level of scrutiny 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Identification and recruitment of willing volunteers for such studies can pose distinct challenges-in a recent study 120,000 potential recruits were contacted to recruit 112 participants 9,10 . One study on the experiences and perceptions of participants in a malaria challenge study in Kenya focussed on ethical considerations appropriate to a malaria endemic setting 11 . There is otherwise a paucity of research on factors motivating participants to enrol in human challenge studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, volunteers may be displaced to a non-endemic region for the study duration. However, the prolonged, seven to 12-week "admission" required for the CHI-S would be a major burden and inconvenience, as opposed to the relatively short-duration (24 days) for malaria CHI studies where such approach has been employed 14 . The possibility of volunteers absconding during the study, given the long duration, might be significant, abrogating the value of such an approach.…”
Section: )mentioning
confidence: 99%
“…HIS can accelerate vaccine development by facilitating an understanding of pathophysiology and mechanics of immune response under highly controlled conditions and to efficiently test vaccine or drug efficacy. The intentional infection of healthy study participants with a viable challenge agent or pathogen under highly controlled conditions [6], could potentially raise public concerns, queries, and ethical complexities particular to LMIC settings; including concerns around communal pressure to participate, local language wording in information sheets, beliefs on blood collection, adequacy of infection control measures in the community, and appropriateness of compensation given levels of poverty [7]. Additionally, the daily risk posed in some LMIC environments makes it difficult to control HIS participants' exposure to additional diseases or the spread of infection into the larger community without residency requirements [7].…”
mentioning
confidence: 99%